2012 IEEE Globecom Workshops 2012
DOI: 10.1109/glocomw.2012.6477780
|View full text |Cite
|
Sign up to set email alerts
|

Quality perception of coding artifacts and packet loss in networked video communications

Abstract: Typical wireless video communication applications involve two important basic chains, namely, coding and transmission. Video coding artifacts and packet losses are often introduced in the chains, respectively, which affect the quality of experience (QoE) of end-users for the delivered contents. In order to provide insights for design of QoE-aware content delivery applications, this paper presents a subjective quality assessment study that investigates the mechanism of quality perception under simultaneous exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The research community has established a body of work that investigated several of the influencing factors [1] for QoE in video-conferencing. In the main focus are the system factors, with aspects like audio and video quality [6,14,40,43,62], audiovisual synchronization [58] and delay [51,59]. Further studies regarding non-technical influencing factors have looked into interaction [20,47,59], the user state, such as engagement [52] and contextual factors like different devices [10,66].…”
Section: Subjective Studies Investigating Qoe In Video-conferencingmentioning
confidence: 99%
“…The research community has established a body of work that investigated several of the influencing factors [1] for QoE in video-conferencing. In the main focus are the system factors, with aspects like audio and video quality [6,14,40,43,62], audiovisual synchronization [58] and delay [51,59]. Further studies regarding non-technical influencing factors have looked into interaction [20,47,59], the user state, such as engagement [52] and contextual factors like different devices [10,66].…”
Section: Subjective Studies Investigating Qoe In Video-conferencingmentioning
confidence: 99%
“…Our preliminary study [15] demonstrated existence of the interaction between the two artifacts in quality perception. Therefore, a systematic subjective quality assessment study is necessary so that the effect of the artifacts on the perceived quality can be quantitatively and qualitatively analyzed.…”
Section: Introductionmentioning
confidence: 96%